Robot-Assisted Laparoscopic and Thoracoscopic Surgery: Prospective Series of 186 Pediatric Surgeries - Navarrete Arellano, Mario; Garibay González, Francisco (Frontiers in Pediatrics, 2019)
Objective: We present the applications and experiences of robot-assisted laparoscopic and thoracoscopic surgery (RALTS) in pediatric surgery. Materials and Methods: A prospective, observational, and longitudinal study was conducted from March 2015 to March 2018 that involved a non-random sample of a pediatric population that was treated with RALTS. The parameters examined were: gender, age, weight, height, diagnoses, surgical technique, elapsed time of console surgery, estimated bleeding, need for hemotransfusion, complications, surgical conversions, postoperative hospital stay, and follow-up. The Clavien-Dindo classification of complications was used. The surgical system used was the da Vinci model, Si version (Intuitive Surgical, Inc., Sunnyvale, CA. U.S.A), with measures of central tendency. Results: In a 36-months period, 186 RALTS cases were performed, in 147 pediatric patients and an adult; 53.23% were male, and the remaining were female. The average age was 83 months, ranging from 3.5 to 204 months, plus one adult patient of 63 years. The stature was an average of 116.6 cm, with a range of 55–185 cm; the average weight was 26.9 kg, with a range of 5–102 kg; the smallest patient at 3.5 months was 55 cm in stature and weighed 5.5 kg. We performed 41 different surgical techniques, grouped in 4 areas: urological 91, gastrointestinal and hepatobiliary (GI-HB) 84, thoracic 6, and oncological 5. The console surgery time was 137.2 min on average, ranging from 10 to 780 min. Surgeon 1 performed 154 operations (82.8%), and the remainder were performed by Surgeon 2, with a conversion rate of 3.76%. The most commonly performed surgeries were: pyeloplasty, fundoplication, diaphragmatic plication, and removal of benign tumors, by area. Hemotransfusion was performed for 4.83%, and complications occurred in 2.68%. The average postoperative stay was 2.58 days, and the average follow-up was 23.5 months. The results of the 4 areas were analyzed in detail. Conclusion: RALTS is safe and effective in children. An enormous variety of surgeries can be safely performed, including complex hepatobiliary, and thoracic surgery in small children. There are few published prospective series describing RALTS in the pediatric population, and most only describe urological surgery. It is important to offer children the advantages and safety of minimal invasion with robotic assistance; however, this procedure has only been slowly accepted and utilized for children. It is possible to implement a robust program of pediatric robotic surgery where multiple procedures are performed.